RETROFITTING OF DAMAGED LINK BEAMS IN BASE AND OUTRIGGER AREAS WITH VISCOELASTIC COUPLING DAMPERS ON 81-STOREY SUPER TALL BUILDING - ADICAHYA - NIM : 25017058, RUBEN
Viscoelastic Coupling Damper (VCD) is a promising damping device that is able to improve structural lateral respons with coupled wall system. VCD provides added damping acting as substitute of link beam deforming in shear. Since damaged link beam is very hard to repair, VCD is expected to omit the damage. Viscoelastic material in VCD has stiffness and damping properties that can be modelled using Generalized Maxwell Model. To limit the generated shear force, VCD is equipped with Reduced Beam Sections (RBS) acting as shear fuse to avoid viscoelastic material tearing. Case study used 81-storey coupled wall building model with outrigger and belt-truss system. The building is located on severe seismic zone, in the capital city of Jakarta, and having soft soil site class. Spectrum response analysis with average seismic response coefficient was used to define seismic forces. Design of structural elements followed the corridor of fully ductile structure with the help of ETABS 2016 program. In this study, link beams were modelled as fiber element which is able to behave inelastically. Nonlinear structure analysis specifically used the help of PERFORM 3D program. Nonlinear static pushover method was used to identify initial link beam damage and to verify structure nonlinear response. Then the result would be validated using nonlinear dynamic time history of Landers earthquake. Only damaged link beams that exceeded yield point would be substituted by VCDs, those were 3 in base area and 1 in outrigger area. Global response of structure was not affected significantly, while surrounding element response was. The damage did not move to another link beams, yet moved to surrounding shear walls so that the use of VCD was not that effective.